Emotional intelligence : why it can matter more than IQ - Goleman, Daniel (New York : Bantam Books, 1995)
In today's fast-paced world, it's tough to find the time to read. But with Joosr guides, you can get the key insights from bestselling non-fiction titles in less than 20 minutes. Whether you want to gain knowledge on the go or find the books you'll love, Joosr's brief and accessible eBook summaries fit into your life. Find out more at joosr.com. Is there something more important than IQ when it comes to a person's future success and happiness? Learn the important role that emotional intelligence has to play in the development of individuals and what you can do to facilitate a better future
Includes bibliographical references (p. 311-339) and index.
Keywords: Emotions; Emotions and cognition; Emotions -- Social aspects